Impacts of Capture Fishery on Income and Its Equity among Fisher Households’ of Tripura - Das, Apu; Kumar, Nalini Ranjan (Indian Journal of Hill Farming, 2018)
The study has assessed the income distribution pattern across fisheries households involved in capture fishery in the state of Tripura. The study is based on the responses of 90 fishers involved in capture fishery and 140 households involved other fisheries activities. The study has revealed that the fishers involved in capture fishery, improving equitable distribution of income across the fishers than households involved in other fishery related activities. The study has suggested proper management of capture fishery will leads to brings more income to the fishers and also it will help to bring more equal distribution of income.